What are the determinants for individuals to undergo cardiovascular disease health checks? a cross sectional survey - Cheong, Ai Theng; Khoo, Ee Ming; Liew, Su May; Chinna, Karuthan (Public Library of Science, 2018)
Background There is a need to improve public’s participation in health checks for early identification of individuals at high risk of CVD for prevention. The objective of this study is to identify significant determinants associated with individuals’ intention to undergo CVD health checks. These determinants could be used to develop effective strategies to improve CVD health check participation.